2020
DOI: 10.1177/1550147719895960
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-specific encephalography standardized low-resolution brain electromagnetic tomography network and gray matter correlations in vascular dementia patients

Abstract: Vascular dementia, secondary to Alzheimer’s dementia, ranks as one of the most frequent dementia types. The process of vascular dementia is divergent with other neurodegenerative dementias and thus reversible at the early cognitive disorder or mild dementia stages. The encephalography and neuroimaging data mining at different stages would bring neuromodulation strategies in practice; 15 mild cognitive impairment patients and 16 mild vascular dementia patients as well as 17 cognitive healthy controls were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Concerning the specificity of EEG interrelatedness measures, Sloan et al (1994) showed no significant differences in rsEEG spectral coherence between ADD vs. major VCI (MID) patients with reduced regional cortical blood flow. Lv et al (2020) reported decreased gamma-band connectivity in mild major VCI group compared with an age-matched CU group.…”
Section: Quantitative Spatial and Frequency Analysis Of Rseeg Rhythms...mentioning
confidence: 91%
See 2 more Smart Citations
“…Concerning the specificity of EEG interrelatedness measures, Sloan et al (1994) showed no significant differences in rsEEG spectral coherence between ADD vs. major VCI (MID) patients with reduced regional cortical blood flow. Lv et al (2020) reported decreased gamma-band connectivity in mild major VCI group compared with an age-matched CU group.…”
Section: Quantitative Spatial and Frequency Analysis Of Rseeg Rhythms...mentioning
confidence: 91%
“…Partanen et al (1997) reported reduced alpha amplitude ratio between eyes closed and eyes open condition in major VCI patients as compared to age-matched CU persons. Loring et al (1985) reported a decrease in 40 Hz activity at rest in major VCI (MID) patients compared to age-matched CU persons, whereas Lv et al (2020) showed an increase of power of gamma for the same comparison.…”
Section: Quantitative Spatial and Frequency Analysis Of Rseeg Rhythms...mentioning
confidence: 95%
See 1 more Smart Citation